The Concept of Islamic Religious Education Management Contained in Surah Luqman Verses 12-19 - Murni Yanto (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2022)
The Qur'an is the absolute source of concepts and their existence does not change even though their interpretation is possible to change according to context or circumstances, times, and places. The Qur'an is a Normative-Theoretical guideline in the implementation of Islamic religious education. The research aims to describe and critically analyze the concepts of Education contained in the Qur'an surah Luqman and its Implementation in Islamic Religious Education. This research is literature research, with data collection techniques carried out through documentation. The approach used in this study is a normative-philosophical approach. The analysis of the data qualitatively is carried out with deductive-inductive analysis instruments. Deductive methods are taken to uncover or generalize the concepts of education in the Qur'an surah Luqman so that a complete conclusion can be obtained. While the inductive method is used.